PENGARUH STAPHYLOCOCCUS AUREUS DALAM RUANGAN TERHADAP SICK BUILDING SYNDROME (SBS) DI PT UNILAB PERDANA, JAKARTA SELATAN - Hendro Wiguno; Nurhayati; Hening Darpito (JURNAL TECHLINK, 2020)
This study aims to obtain information and determine the effect of Staphylococcus aureus in the room against sick building syndrome (SBS) on front office employees and operational space at PT Unilab Perdana, South Jakarta. The location of the study was conducted at PT Unilab Perdana, South Jakarta. When the study was conducted in March to July 2019. The results showed that: the influence of SBS symptoms at the front office location were 44 people, an average of 9 colonies of staphylococcus aureus bacteria. While the influence of SBS symptoms in the operational space location was 64 people, with an average of 18.3 colonies of staphylococcus aureus bacteria. The number of employees in the operational room experienced a frequency of Sick Building Syndrome (SBS) complaints dominated by headaches, fatigue, difficulty concentrating and nausea and dizziness with a category 1-3 times as many as 8 people (53.33%). The cause of the number of employees who are in the operational room experiences the frequency of Sick Building Syndrome (SBS) complaints because of the large number of employees who are in the operational space location, and employee activities are centralized in the operational space. Thus, there is an effect of the number ofstaphylococcus aureus bacterial colonies in the room on Sick Building Syndrome (SBS) in front office employees and the operating room of PT Unilab Perdana, South Jakarta. The dominance of symptomsand frequency of Sick Building Syndrome (SBS) complaints occurred in employees in the operatingroom of PT Unilab Perdana, South Jakarta